Perlindungan Hak Asasi Manusia Terhadap Perempuan Di Daerah Konflik - Astuti Nur Fadillah; Jacob Hattu (Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Humans as creatures created by God Almighty have basic rights inherent in themselves that must be protected, besides that humans, fellow creatures of God, should be obliged to respect other human rights.Purposes of the Research: The research aims to be able to analyze the Protection of Human Rights Against Women in Conflict Areas.Methods of the Research: The research method used is normative juridical research.Results of the Research: Conflicts in several countries cannot be avoided, and until now conflicts still occur in several countries. The conflict that occurred gave fear and a feeling of insecurity for the community. In essence, conflict cannot be separated from acts of violence and can cause material and psychological losses. Violence that occurs in armed conflicts usually does not only happen to men but also occurs to women. Sexual violence in armed conflicts in humanitarian law refers more to acts of attacking women's reputation for honor. The presence of human rights instruments must be a guideline for the protection of women's rights so that they are no longer victims of violence. In addition, women must also be given the opportunity to participate in conflict resolution.